2003
DOI: 10.1002/chir.10196
|View full text |Cite
|
Sign up to set email alerts
|

Additive concentration effects on enantioselective separations in supercritical fluid chromatography

Abstract: Polar additive concentration effects in supercritical fluid chromatography were studied on chiral stationary phases having either a macrocyclic glycopeptide or a derivatized polysaccharide as the chiral selector. Two basic additives, isopropylamine and triethylamine, were incorporated into the methanol modifier at various concentrations and the effects on retention, selectivity, and resolution were monitored. Many of the analytes failed to elute from the macrocyclic glycopeptide stationary phase in the absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Conversely, in the NP mode, the amount of ethanol, the more polar solvent in the hexane/ethanol NP mobile phases, was increased to adjust the retention factors. 16 …”
Section: Stationary Phase Polaritymentioning
confidence: 97%
See 2 more Smart Citations
“…Conversely, in the NP mode, the amount of ethanol, the more polar solvent in the hexane/ethanol NP mobile phases, was increased to adjust the retention factors. 16 …”
Section: Stationary Phase Polaritymentioning
confidence: 97%
“…16,17 Thermodynamic studies showed different results depending on the chromatographic mode, i.e., on the mobile phase nature. NP and RP modes produced only enthalpy driven enantiomer separations.…”
Section: Solvent Effectsmentioning
confidence: 98%
See 1 more Smart Citation
“…The effects of two basic additives, isopropylamine and TEA, in SFC separations were investigated on Chirobiotic V and Chiralpak AD CSPs using a test set of 12 basic compounds [22]. The compounds that could be separated are indicated in Tables 3 and 4.…”
Section: Separations On Polysaccharide-based Cspmentioning
confidence: 99%
“…A control reaction using heat treated cells afforded no carboxylation product, either, which indicates that a biocatalyst is at work and that the carboxylation is not an unexpected process promoted by non-enzymic constituents of the cell. Extraction Extraction of caffeine from coffee beans [11], extraction of oil from corn fiber [12], extraction of compounds with pharmaceutical importance from microalgae [13], enantioseparation of chiral alcohols by complex formation and subsequent supercritical fluid extraction [14] Chromatography Separation of fatty acids [15], separation of enantiomers [16], supercritical fluid chromatography-mass spectrometry [17], two-dimensional supercritical fluid chromatography [18] Reactions Hydrogenation of supercritical CO 2 to formic acid, alkyl formates, and formamides by homogeneous catalysts [19,20], enantioselective hydrogenation of imines in supercritical CO 2 by iridium-catalyst [21], hydroformylation in supercritical CO 2 by rhodium catalysts [22], asymmetric Diels-Alder reactions in supercritical CO 2 catalyzed by rare earth complexes [23] Other Polymer coating/encapsulation of nanoparticles using a supercritical anti-solvent process [24], improvement of insulin absorption from intratracheally administrated dry powder prepared by a supercritical CO 2 process [25], dyeing of natural fibers from perfluoropolyether reverse micelles in supercritical CO 2 [26] Scheme 1. [49].…”
Section: Carboxylationmentioning
confidence: 99%